THE IMPACT OF CAPITAL STRUCTURE ON ISLAMIC BANKS PROFITABILITY: EVIDENCE FROM GCC COUNTRIES - Moustapha, Larabi; Benziane, Roucham (Indian Journal of Finance and Banking, 2022)
This paper aims to reveal the relationship between capital structure variables and the Profitability of Islamic banks. The examination has been performed using panel data for a sample of 05 Islamic banks operating in the Gulf Cooperation Council GCC countries (2010-2020). Capital Structure is measured by Deposit to Total Assets (DTA) and Equity to Total Assets (ETA) ratio. In contrast, return measures Profitability on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Data collected were analyzed by using E-Views10 software. The research results indicate that the ETA ratio has a positive and significant relationship with ROA. Whereas, The Deposit to Total Assets (DTA ratio) has no significant relationship with Return on asset (ROA). There is an insignificant relationship between (ETA ratio, DTA ratio) and the ROE ratio. Moreover, there is a significant solid effect between the ETA ratio and Net Profit Margin (NPM). At the same time, there is no significant relationship between the DTA ratio and Net Profit Margin (NPM). Therefore, the study can guide The GCC Islamic bank executives, The Shariah Supervisory Board, and the decision-makers in the GCC area to rely on specific capital structures for Islamic banks to improve their profitability. JEL Classification Codes: G32, L25, G21, C23, C33.